Chiral helical supramolecular hydrogels with adjustable pitch and diameter towards high-performance chiroptical detecting. (December 2021) - Yang, Li; Su, Nan; Huang, Juexin; Dou, Xiaoqiu; Zhao, Changli; Feng, Chuanliang
Highlights: Negatively charged chiral phenylalanine-derived hydrogelators and positively charged carbon dots can co-assemble into nanofibrous supramolecular hydrogels. The degree of helical pitch and the diameter of these co-assembled nanofibers can be tailored by achiral carbon dots, thus further to affect their chiroptical performance. The nanofibers with the largest helical pitch and smallest diameter show the highest luminescence dissymmetry g-factors ( g lum ), which are used to efficiently differentiate between left and right circularly polarized light. Abstract: Helical architectures with adjustable helical parameters and chiroptical functions are expected to play a fundamental role in biomedicine and nanoscience fields but is still in its early stage of study. Herein, chiral phenylalanine-derived hydrogelators ( D G1 and L G1) can self-assemble into left-handed or right-handed helical nanofibrous hydrogels. Achiral carbon dots with different charges are co-assembled with D G1 or L G1 through electrostatic interactions and hydrogen bonds, helical supramolecular hydrogels with controllable helical pitch and diameter are readily obtained. Typically, the co-assembled hydrogels show both circular dichroism (CD) and circularly polarized luminescence (CPL) signals in the absorption regions. The nanofibers with the largest helical pitch and smallest diameter show the highest luminescence dissymmetry g -factors ( g lum ) up to -3.80 × 10 −3, which are able to efficiently differentiate between left and right circularly polarized light. This work not only paves a universal method to obtain chiral helical nanostructures with adjustable pitch and diameter, but also shines light on these advanced helical nanostructures for potential applications in chiroptical detectors. Graphical abstract: Negatively charged chiral phenylalanine-derived hydrogelators and positively charged carbon dots can co-assemble into nanofibrous supramolecular hydrogels. The degree of helical pitch and the diameter of these co-assembled nanofibers can be tailored by achiral carbon dots, thus further to affect their chiroptical performance. Image, graphical abstract